Trophic niche and feeding strategy of the White Stork (Ciconia ciconia) during different phases of the breeding season. (1st February 2015) - Chenchouni, Haroun; Si Bachir, Abdelkrim; Alrashidi, Monif
Assessing feeding conditions and variations of diet composition over the breeding season is of great help in the understanding of the ecological niche of species. In meeting this aim, the White Stork's (Ciconia ciconia) diet was studied based on the analysis of 87 regurgitation pellets collected from Batna (Northeast Algeria). A set of 2138 prey-items were identified and classified into 61 different prey-species belonging to seven classes, 13 orders, 29 families and 51 genera. The White Stork has a diverse diet (food niche breadth, FNB = 14.5, Shannon index H' = 4.4 bits), mainly composed of arthropods, of which 94% of prey-items are insects that represent 8% of total prey biomass. The White Stork constantly fed on the remains of chicken foraged from rubbish dumps (biomass = 68.74%) and small mammals (biomass = 14.41%) as these prey categories constitute a source of high energy, particularly during the period of chick rearing. GLMs applied for diet characteristics revealed a significant variation in numbers of prey individuals between breeding phenological stages. While variations of other diet parameters (biomass, species richness, FNB, H', H'max and evenness) were not statistically influenced by breeding phenology. All diet characteristics were significantly correlated with the period of chick development, which is the key period for breeding success; suggesting an increase in parental investment and feeding effort. Our findings suggest that the White Stork performs a balance in order to satisfy its food requirements by compensating reciprocally between intake of prey numbers and their biomass regardless of the phenological stage of reproduction.